SAT0017 Synovial Membrane Hypertrophy and Power Doppler Positivity Predict Clinical Relapse in Long-Standing RA Patients Reaching DAS Disease Remission Under Biologic Treatment: Prospective 5 Years Follow-Up Real-Life Analysis. (23rd January 2014) - Alivernini, S.; Peluso, G.; Gigante, M. R.; Fedele, A. L.; Giammarioli, E.; Berardi, G.; Correra, M.; Canestrari, G. B.; De Luca, G.; Rucco, M.; Simone, D.; Tolusso, B.; et al.
Abstract : Background: Persistent disease remission is the major goal of Rheumatoid arthritis(RA) treatment. Current clinical score methods do not reflect the inflammation at the primary site of RA pathology and no clear clinical parameters arose to be associated with disease flares. Ultrasonography(US) has a superior sensitivity in detecting synovial hypertrophy(SH) and its activity through Power Doppler(PD) in RA. Objectives: To assess if the SH presence and PD signal at US evaluation could predict clinical relapse in RA patients achieving disease remission in a prospective 5 years analysis. Methods: RA patients in disease remission(DAS44<1, 6 twice 3 months apart) were enrolled. At the time of clinical remission each RA patient underwent US evaluation of bilateral wrists (radiocarpal-intercarpal), II-III MCP and II-III PIP joints. SH and PD signal were assessed using a semiquantitative score 1 . RA patients were stratified in 3 subgroups based on SH and PD positivity as "true US remission"(SH-/PD-), "partial US remission"(SH+/PD-) and "no US remission"(SH+/PD+)respectively. RA patients were followed for 5 years from disease remission and disease relapse rate was recorded. Results: 122 RA patients (72 with long-standing(LSRA) and 50 with early(ERA)) in disease remission underwent US evaluation. Among the general cohort, 28, 7%RA patients had "true US remission", 36, 9%"partial US remission" and 34, 4%"no US remission". RA patients in "no and partial US remission" were more likely IgA-RF positive than RA patients in "true US remission"(p=0, 03). Dividing RA patients based on disease duration, LSRA patients had more likely "partial US remission" whereas ERA patients showed more likely "real US remission", despite clinical remission. Moreover, LSRA patients showed more likely SH presence(80, 6% vs 58, 0% in LSRA and ERA respectively, p=0, 01) and higher total SH score(4, 1±4, 1 vs 2, 0±3, 0; p=0, 03) compared to ERA patients in clinical remission. Among the whole cohort, 87 RA patients(41 LSRA and 46 ERA) were followed for 5 years. LSRA patients had higher relapse rate(48, 8%) compared to ERA patients (19, 6%; p=0, 01). LSRA patients who relapsed were more ikely smokers(p=0, 04), anti-CCP positive (p=0, 01), had positive PD signal (p=0, 02) and a higher PD total score(p=0, 05) compared to LSRA without any flares. A direct correlation between SH total score and PD total score was found in both LSRA and ERA patients achieving remission (r=0, 50;p<0, 0001). After logistic regression analysis, in the whole RA cohort, baseline anti-CCP positivity [OR 3, 14(95%CI:1, 01-11, 59);p=0, 03] and SH presence [OR 4, 77(95%CI:1, 15-19, 69);p=0, 03] arose as independent factors associated to clinical relapse. Moreover, in LSRA patients, anti-CCP positivity [OR 10, 45(95%CI:1, 58-69, 24);p=0, 01] and PD signal positivity [OR 10, 06(95%CI:0, 73-138, 53);p=0, 03] arose as independent factors of clinical relapse within 5 years of remission achievement. Conclusions: US may be a useful tool in the routine assessment of RA patients reaching clinical remission allowing to identify the real US remission status and the possible candidates to drug-free remission. References: PelusoG et alARD2011 Disclosure of Interest: None Declared